2015
DOI: 10.4049/jimmunol.1402383
|View full text |Cite
|
Sign up to set email alerts
|

Natural Anti-Intestinal Goblet Cell Autoantibody Production from Marginal Zone B Cells

Abstract: Expression of a germline VH3609/D/JH2 immunoglobulin heavy chain in mice results in the generation of B1 B cells with anti-thymocyte/Thy-1 glycoprotein autoreactivity (ATA) by co-expression of Vk21-5/Jk2 light chain leading to production of serum IgM natural autoantibody. In these same mice, the marginal zone B cell (MZ B) subset in spleen shows biased usage of a set of immunoglobulin light chains different from B1 B cells, with 30% having an identical Vk19-17/Jk1 light chain rearrangement. This VH3609/Vk19-17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…This BCR recognizes the highly glycosylated Thy‐1 glycoprotein abundantly expressed on immature thymocyte membranes, including those of dying thymocytes. Generation of V H 3609μTg mice, as well as VDJ knock‐in mice, revealed generation of mature B1a cells with this ATA BCR in the presence of self‐antigen, whereas there was no B1a cell generation in the absence of Thy‐1, demonstrating for the first time that positive selection occurs in mouse B cells, as has long been recognized for T cells.…”
Section: Differences In Bcr Signal Strength Generate B Cell Subsets Pmentioning
confidence: 78%
See 1 more Smart Citation
“…This BCR recognizes the highly glycosylated Thy‐1 glycoprotein abundantly expressed on immature thymocyte membranes, including those of dying thymocytes. Generation of V H 3609μTg mice, as well as VDJ knock‐in mice, revealed generation of mature B1a cells with this ATA BCR in the presence of self‐antigen, whereas there was no B1a cell generation in the absence of Thy‐1, demonstrating for the first time that positive selection occurs in mouse B cells, as has long been recognized for T cells.…”
Section: Differences In Bcr Signal Strength Generate B Cell Subsets Pmentioning
confidence: 78%
“…The generation of anti‐thymocyte/Thy‐1 autoreactive (ATA) BCR transgenic and knock‐in mouse lines enabled us to test the important role of BCR signaling in B1a cell generation, and the differences in B cell fate arising from different levels of BCR signaling in B‐1 and B‐2 development . The unmutated ATA IgM (V H 3609/V k 21) was originally identified as a B1a cell BCR in SM/J mice that are non‐autoimmune but are known to have an elevated level of ATA IgM autoantibody in the serum .…”
Section: Differences In Bcr Signal Strength Generate B Cell Subsets Pmentioning
confidence: 99%
“…Few 24E1 + cells detected in MZ B and FO B cells were 24E1 med cells (Figure 3c); single cell Igκ sequence analysis revealed that 24E1 med cells utilized different V k 9-J k junctional residues (Figure 3c). The mouse MZ B cell pool is known to contain autoreactive B cells 26, 38 , as with B1 B cells. To assess whether the MZ B cell can include the stereotyped AMyIIA BCR, a V H Q52/D/J-μ a IgH transgenic mouse line, OK44, was generated as previously described 14 (Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Rag1 −/− mice were used for producing ethanol-fixed frozen tissue sections, and microscope imaging was done as described previously 26, 27 . 1/100 diluted hybridoma IgM ascites (2–10 μg/ml) were incubated on tissue section slides for 90 minutes at 37°C, followed by AlexaFluor (AF) 488 anti-IgM (331.12), together with DAPI (Thermo Scientific), with or without PE-anti-CD31 (eBioscience) (30 minutes at RT).…”
Section: Methodsmentioning
confidence: 99%
“…Early adoptive transfer studies showed that much of the circulating IgM was produced by these cells and subsequent studies using transfer of B‐1 cells into neonatal B cell‐depleted mice showed that amount to be more than 90% . Others reported that marginal zone (MZ) B cells also contribute to natural antibody production in both humans and mice …”
Section: Natural Igm Production: Two Sides To a Coinmentioning
confidence: 99%